Hypertensive heart disease in Africa - Aje, Akinyemi; Adebiyi, Adewole A.; Falase, Ayodele O. (SA Heart Journal, 2017)
Hypertension has become an important public health problem in Africa. Currently an epidemiologic transition from infectious diseases is going on in the continent and the prevalence of chronic diseases like hypertension is increasing. The response of the heart to the stress/afterload imposed on the left ventricle by the progressively increasing arterial blood pressure is described as hypertensive heart disease. Hypertensive heart disease and failure are the commonest cardiovascular diseases of Africans. Since hypertension is a treatable cardiovascular risk factor, there is need to create more awareness about the disease and educate our patients concerning drug compliance. There is also a need for longitudinal multicentre study in Africa, in order to assess the severity and burden of the disease.